Students’ Points of View About Learning English as a Foreign Language Through Communication and Interaction in 9-Year Elementary Schools (Albanian Context) - Kapurani, Evis (European Journal of Multidisciplinary Studies, 2016)
Communicative Language Teaching (CLT) is an interactive method which helps learning English language through communication, in a theoretical point of view CLT is a more effective method compared with traditional methods such as Grammar Translation Method and Audio lingual Method, and it is a preferred method to be used nowadays in foreign language learning. This is a descriptive study which aims to analyze and discover the 9-year elementary schools students’ opinions and points of view about learning a foreign language based on the principles of contemporary interactive student-centered methods and traditional ones. It is introduced a theoretical analyses about methods of language teaching in general, characteristics description and principles of CLT, accuracy and fluency in CLT, teacher and student role, communicative competence, CLT application, significance, impact, comparison of CLT with traditional methods. The data are collected from students of 9-year elementary schools on sixth, seventh, eighth and ninth grades through a survey questionnaire. Questions on the questionnaire are focused on finding students’ opinions and points of view about language learning in a certain context in practice, according to their needs and preferences on learning a language based on CLT premises about communication, accuracy, fluency, learning grammar and vocabulary, teacher roles etc. and principles of other traditional methods. Results are converted into percentages which show students preferences about the way they are used to, need and want to learn a foreign language and with which principles of the foreign language teaching methods they agree or not. Findings are described and analyzed according to their relation with theoretical issues. From the analyses it results that using CLT may prove to be a very successful method in both learning and teaching because students welcome the principles used in this method despite their “attachment” to the principles of previous teaching methods that they are used to.